Failure rate after primary anterior cruciate ligament reconstructions - Alabri, Ibrahim M.; Allawati, Ali A. (International Journal of Research in Orthopaedics, 2025)
Background: One of the most common sport injuries is anterior cruciate ligament injury, making anterior cruciate ligament reconstruction (ACL) a very common orthopaedics procedure. Arthroscopic anterior cruciate ligament reconstruction can be performed using auto-graft from different sources like, bone patellar tendon graft, hamstring tendons (semitendinosus with or without gracilis) or peroneus longus tendon. Methods: A retrospective study of total 230 patients operated from June 2017 until December 2020. All of then underwent primary arthroscopic anterior cruciate ligament (ACL) reconstructions using hamstring tendons auto-graft. The others underwent revision ACL; their primary surgery was done in other hospital. Results: Statistically, total rate of complications after primary ACL reconstructions, which was defined as the need for revision surgery, was five patients (2.17%) for home revision was done using contra lateral hamstring graft. Conclusions: A failure rate of 2.17 percent over the reported period of three years falls within reported rates in literature.